The Attacking Process in Football: A Taxonomy for Classifying How Teams Create Goal Scoring Opportunities Using a Case Study of Crystal Palace FC - Kim, Jongwon; James, Nic; Parmar, Nimai; Ali, Besim; Vučković, Goran (Frontiers in Psychology, 2019)
Purpose: Whilst some studies have comprehensively described the different features associated with the attacking process in football they have not produced a methodology of practical use for performance enhancement. This study presents a framework of comprehensive and meaningful metrics to objectively describe the attacking process so that useful performance profiles can be produced. Methods: The attacking process was categorised into three independent situations, no advantage (stable), advantage, and unstable (potential goal scoring opportunity) situations. Operational definitions for each situation enhanced their reliability and validity. English Premier League football matches (n=38) played by Crystal Palace Football Club in the 2017/2018 season were analysed as an exemplar. Results: Crystal Palace FC created a median of 53.5 advantage situations (IQR=16.8) and 23 unstable situations (IQR=8.8) per match. They frequently utilised wide areas (Median=21.5, IQR=9.8) to progress, but only 26.6% resulted in unstable situations (Median=6.0, IQR=3.8), the lowest rate compared to the other advantage situations. Conclusion: This classification framework, when used with contextual factors in a multi-factorial manner, including individual player contributions, will provide practically useful information for applied practice. This approach will help close the so called theory-practice gap and enable academic rigour to inform practical problems.